Providing Out-of-School Girls with Skills : A Review of the Global Evidence - Khan, Ayesha; Mupuwaliywa, Mupuwaliywa (World Bank, Washington, DC, 2016)
Promoting relevant technical and life skills is one option to empower adolescent girls by increasing their capacity to generate income and therefore by enhancing their bargaining power within the household. This Note presents a situation analysis of the current skills set and employment outcomes of adolescents (aged 15-19 years) in Zambia, with a focus on adolescent girls. The main source of data is several rounds of the Zambia Labor Force Survey (years 2005, 2008, 2012). The data reveal that although adolescent girls are more economically active than their male counterparts, they are also more likely to be engaged in part-time employment, be unemployed, and earn less than their male counterparts. However, little is known about how these trends affect choices made by adolescent girls and their households.